2005
DOI: 10.1103/physreve.72.021309
|View full text |Cite
|
Sign up to set email alerts
|

Rheophysics of dense granular materials: Discrete simulation of plane shear flows

Abstract: We study the steady plane shear flow of a dense assembly of frictional, inelastic disks using discrete simulation and prescribing the pressure and the shear rate. We show that, in the limit of rigid grains, the shear state is determined by a single dimensionless number, called inertial number I, which describes the ratio of inertial to pressure forces. Small values of I correspond to the quasistatic regime of soil mechanics, while large values of I correspond to the collisional regime of the kinetic theory. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

113
1,212
8
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,021 publications
(1,336 citation statements)
references
References 100 publications
(203 reference statements)
113
1,212
8
3
Order By: Relevance
“…The corresponding mechanical parameters, namely the normal and shear stiffness k n and k s (elasticity parameters), the restitution coefficient e (viscous parameter) and the friction coefficient µ are summarized in Table 1. The value of the normal stiffness k n was chosen in such a way that the normal interpenetration at contacts are kept small, i.e., to work in the quasi-rigid grain limit (da Cruz et al, 2005;Roux and Combe, 2002). Concerning the normal restitution coefficient e, we verified that the results presented below, and more generally all the macroscopic mechanical quantities obtained from the simulations, are actually independent of this parameter (in the range 0.1-0.9).…”
Section: Contact Lawsupporting
confidence: 49%
See 2 more Smart Citations
“…The corresponding mechanical parameters, namely the normal and shear stiffness k n and k s (elasticity parameters), the restitution coefficient e (viscous parameter) and the friction coefficient µ are summarized in Table 1. The value of the normal stiffness k n was chosen in such a way that the normal interpenetration at contacts are kept small, i.e., to work in the quasi-rigid grain limit (da Cruz et al, 2005;Roux and Combe, 2002). Concerning the normal restitution coefficient e, we verified that the results presented below, and more generally all the macroscopic mechanical quantities obtained from the simulations, are actually independent of this parameter (in the range 0.1-0.9).…”
Section: Contact Lawsupporting
confidence: 49%
“…Discrete element (DE) modeling (Cundall and Strack, 1979) allows computing the motion of a large number of small grains by solving dynamic equations for each and defining a contact law between the grains. In addition, the DE method allows assessing mechanical quantities such as stress, displacement, deformation rate, porosity, etc., computed over representative elementary domains at each material point within the sample.…”
Section: Motivation and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Many studies on the frictional properties of dense granular matter have been conducted also in the field of statistical physics mainly by means of numerical simulation [GDR MiDi, 2004;da Cruz et al, 2005;Jop et al, 2006;Hatano, 2007]. These previous studies have revealed that the friction coefficient of granular matter is described as an increasing function of nondimensional velocity known as the inertial number I.…”
Section: Introductionmentioning
confidence: 99%
“…These previous studies have revealed that the friction coefficient of granular matter is described as an increasing function of nondimensional velocity known as the inertial number I. For example, a constitutive law proposed by da Cruz et al [2005] is…”
Section: Introductionmentioning
confidence: 99%